Effects of Social Constructivist Learning Environment Design on 5th Grade Learners' Learning - Akyol, Semra; Fer, Seval (ELSEVIER SCIENCE BV, 2010)
The aim of this study was to determine the effects of 'Social Constructivist Learning Environment' (SCLE) on the 5(th) grade primary school learners. The study sample was composed of seven 5th grade learners attending at the primary schools in Istanbul, Turkey. In this qualitative study, a focus group method was used with a phenomenological approach. In the scope of the study, semi-structured focus group interviews were conducted and analyzed using the method developed by Miles and Huberman (1992). Analyses showed that SCLE design is effective on learning of learners and on provision of learners with new information through group work and multimedia. At the end of the study, SCLE design was concluded to have a positive effect on learning outcomes. (C) 2010 Published by Elsevier Ltd.
Keywords: Social constructivist learning environment; learning; teaching; instructional design; Education & Educational Research